2018
DOI: 10.1002/ijc.31914
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year recurrence rates for breast cancer subtypes in the Netherlands: A large population‐based study

Abstract: Here we report for the first time the relation between breast cancer subtypes and 10‐year recurrence rates and mortality in the Netherlands. All operated women diagnosed with invasive non‐metastatic breast cancer in 2005 in the Netherlands were included. Patients were classified into breast cancer subtypes according to ER, PR, HER2 status and grade: luminal A, luminal B, HER2 positive and triple negative. Percentages and hazards of recurrence were compared among subtypes. Adjusted 10‐year overall (OS) and recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 42 publications
5
83
0
3
Order By: Relevance
“…[7][8][9] Other studies have reported worse outcomes for patients with lobular BC after ≥6 years of follow-up. 10,11 Pleomorphic lobular BC is a rare, more aggressive variant of lobular BC and appears to have a dismal prognosis. 12,13 Cancer November 15, 2020…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Other studies have reported worse outcomes for patients with lobular BC after ≥6 years of follow-up. 10,11 Pleomorphic lobular BC is a rare, more aggressive variant of lobular BC and appears to have a dismal prognosis. 12,13 Cancer November 15, 2020…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, these findings should be cautiously taken into account because follow‐up was quite short, being no more than 24 months. HER2‐positive and triple‐negative breast cancers are associated with early events, but luminal cancers (the majority of cases in this series) are more frequently late‐recurring, thus possible recurrences may be missed in the present study …”
Section: Discussionmentioning
confidence: 77%
“…HER2-positive and triple-negative breast cancers are associated with early events, but luminal cancers (the majority of cases in this series) are more frequently late-recurring, thus possible recurrences may be missed in the present study. 26 No differences were observed in surgery time between ROLL and TCC (respectively, 65 vs 62.9 minutes) despite operative time 34,35 Most of the previous studies were designed before the recent definition of adequate margins for invasive cancer and DCIS, and frequently patients with benign or uncertain lesions were included, conversely to the present study. 8,[27][28][29][30][31][32][33] Furthermore, adequacy of resection has been often evaluated on specimen volumes or weight, kind of studies since adequacy of resection is the main end-point for breast-conserving surgery of nonpalpable cancers, and current imprecisions and heterogeneity in volumes measurement have led to inconsistent or controversial results.…”
Section: Mass-like Lesions Such As Nodules or Distortions Have Been Omentioning
confidence: 79%
“…The risk of developing brain metastases for the basal-like and HER2-positive subtypes is four times greater than for the luminal A/B subtypes [17]. Moreover, basal-like and HER-2-positive tumors are associated with early relapse [18,19].…”
Section: Metastatic Dissemination Pattern Of Breast Cancermentioning
confidence: 99%